Peluang Peluang dan tantangan pengembangan teknologi Oscilating Water Column (OWS) di Indonesia. - sigit arrohman; Dwi Aries Himawanto (Jurnal Energi dan Teknologi Manufaktur, 2021)
Renewable energy is one of the government's efforts to increase the source of the national electricity supply and reduce fossil energy sources. Indonesia has the potential to develop renewable energy in the fields of ocean waves, sunlight, water, and geothermal. But of all these, the most promising to become renewable energy development opportunities are water energy, geothermal energy and ocean wave energy. Indonesia as an archipelagic country with an area of ​​1,904,556 km2 which consists of; 17,508 islands, 5.8 million km2 of ocean and 81,290 million km of beach length, the potential for marine energy, especially ocean waves, is very potential to be empowered as new and renewable alternative primary energy, especially for power generation. This ocean wave power plant has been widely developed, including: buoy type technology, overtopping devices technology, oscillating water column technology. Oscillating Water Column (OWC) is an alternative technology to convert ocean wave energy using an oscillating water column system. The ocean wave conversion technology of the OWC system was chosen because it is suitable in areas with steep coastal topography and has a wave height value between 0.2 m to 1.19 m and even exceeds so that the electricity generated is greater. OWC technology which will be developed for the territory of Indonesia has several opportunities and challenges. Opportunities and challenges that will be faced include the potential for waves, the application of OWC to waterways in Indonesia, OWC systems, and technology investment for the prospect of long-term energy development in Indonesia.